Pengaruh Bahasa Arab Terhadap Penetapan Hukum Islam (Analisis Terhadap Kosa Kata Musytarak/Ambigu di dalam Al-Qur’an) - Kamaluddin Abunawas (Jurnal Adabiyah: Humanities and Islamic Studies, 2012)
Arabic language as a language used in al-Quran has wide meaning and various language  expression that enable some experts of Islamic law have difference in understanding the the texts, thus it brings about the difference in determining law. it is due to the ambiguitive text existing in al-Quran. The ambiguity is caused by singular words, or singular words which grammatically has different characters, as well as ambiguity due to plural words.